(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article evaluates the spatial distribution and hazard levels of surface water erosion on rainfed soils of the Chatkal mountain range based on 3D modeling. The study employs remote sensing data, a digital elevation model (DEM), and geographic information system (GIS) technologies. Topographic factors, vegetation cover, and soil moisture conditions influencing erosion processes are analyzed in an integrated manner. Based on the obtained results, areas with low, moderate, and high erosion risk are identified. The developed 3D model has significant scientific and practical importance for visual assessment of erosion processes and for effective land resource management.